The Access to Open Data and Re-use of Public Sector Information: The Polish Perspective .......... 283 - Kawczyńska, Monika (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
This article presents legal regulations applicable in Poland regarding the reuse of public sector information and access to open data. The right to reuse public sector information is a subjective right conferred upon individuals by the European Union, which is a law that the national authorities of the member states must ensure to its full effectiveness. It was first introduced into the Polish legal order in 2011 as a marginal addition to the already existing act on the access to public information. Currently it is regulated by the elaborated Act of 11 August 2021 on open data and the reuse of public sector information, which goes beyond the minimum set of requirements provided by Directive (EU) 2019/1024. An empirical study of the application of the new act, within a year of its entry into force, was carried out for the purpose of this article. The focus of the research was the practical application of the new regulations in various public institutions, libraries, museums, archives and companies performing public tasks. The statistical research also dealt with the appeals procedure to the minister of digitalisation, who was designated as the single appeal authority for the entire national territory in disputes concerning the reuse of public sector information. In addition, the practicalities of making public sector information available on the official open data portal were assessed.